Molecular Characterization of Noroviruses and Rotaviruses Involved in a Large Outbreak of Gastroenteritis in Northern Italy - Di Bartolo, Ilaria (American Society for Microbiology, 2011)

(untitled)
Noroviruses and rotaviruses from a gastroenteritis outbreak affecting >300 people near Garda Lake (Northern Italy) in 2009 were investigated. Characterization of viruses from 40 patient stool samples and 5 environmental samples identified three distinct rotavirus and five norovirus genotypes; two of the latter were detected in both patient and environmental samples.